PENGEMBANGAN BUMDES MELALUI PENYESUAIAN KEBIJAKAN PEMERINTAH DALAM MENJEMPUT INDONESIA EMAS DARI TIMUR - Nurkhalik Wahdanial Asbara; Mariah; Raden Wirawan; Danial; Indah Suryani Nawing; Putri Nurjannah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This activity is a striking phenomenon and requires serious attention from various parties. To overcome this problem, the results of the activities resulted in recommendations for more responsive policy reformulation, strengthening the capacity of human resources through training, and increasing synergy and partnerships between BUMDes, the government, and the private sector. Optimizing the utilization of local potential is also the key, where BUMDes can develop businesses based on natural resources and local wisdom. The implementation of this ideal concept is expected not only to increase the economic independence of villages, but also to reduce the development gap between the eastern and western regions of Indonesia. The methods used are training and counseling methods. The result of this service activity is to formulate and implement the ideal concept for the development of Village-Owned Enterprises (BUMDes) as an economic pillar at the village level. Through an in-depth analysis of existing policies and challenges, it was found that there was a gap between government policies and practices in the field, limited capital, and low managerial capacity of BUMDes managers.